Integration of Fiqh al-Biʿah into Fiqh al-Watan: An Analysis of Maqasid, Cosmology, and Tadbir Urus al-‘Alam in the State of Pahang - Azman Yusof; Azhar Jaafar; Rahimin Affandi Abd Rahim; Amran Muhammad (Universitas Negeri Padang, 2025)
This article discusses the theory and application of Fiqh al-Bīʿah Watan (Local Islamic Environmental Jurisprudence) as a framework for Islamic environmental governance in the State of Pahang. The approach emphasizes that environmental stewardship is not merely a human duty but an act of worship grounded in tawḥīd, maqāṣid, and adab. Using historical and content analysis, the study examines key policy documents and academic sources such as Garis Panduan Syariah Alam Sekitar (JAKIM, 2023) and Ceramah Aspirasi Pahang 1st (2025). Findings reveal that Fiqh al-Bīʿah Watan functions as a local Islamic epistemology integrating Malaysia customs, science, and Shariah principles within a holistic maqāṣid-based sustainability framework. Pahang thus emerges as a model of Islamic ecological governance aligning development with raḥmah, mīzān, and barakah.